2013
DOI: 10.1111/1750-3841.12230
|View full text |Cite
|
Sign up to set email alerts
|

Czech Ethanol‐Free Propolis Extract Displays Inhibitory Activity against a Broad Spectrum of Bacterial and Fungal Pathogens

Abstract: Propolis acts primarily as a biocide against invasive bacteria and fungi in the hive, suggesting its potential for industrial applications. In food application, propolis is considered as a chemical preservative in meat products, extending shelf life of frozen meat and other food. The mechanism of action is still unclear due to the synergy of multiple compounds contained in propolis and due to parallel targeting of multiple pathways within each affected organism. Here, we examined the antimicrobial properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
2
28
0
5
Order By: Relevance
“…Due to ethanol is natural antibacterial activity, the evaluation of only propolis without diluent anti-bacterial effect is impossible. On the other hand, non-alcoholic diluent including dimethyl sulfoxide (DMSO) is suitable for some alcoholic limitation or diabetic patients and in some papers was noted that propolis activity was developed by DMSO diluent [10]. Our results showed that in the agar diffusion test with paper disks no growth inhibition zone was seen around control disks with methanol that is confirmed by Sawaya et al [4].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Due to ethanol is natural antibacterial activity, the evaluation of only propolis without diluent anti-bacterial effect is impossible. On the other hand, non-alcoholic diluent including dimethyl sulfoxide (DMSO) is suitable for some alcoholic limitation or diabetic patients and in some papers was noted that propolis activity was developed by DMSO diluent [10]. Our results showed that in the agar diffusion test with paper disks no growth inhibition zone was seen around control disks with methanol that is confirmed by Sawaya et al [4].…”
Section: Discussionsupporting
confidence: 82%
“…The results of the study showed that the strongest effect against different type of bacteria was demonstrated by dilution 20% and 60% by diluent in methanol and DMSO, respectively, while the least potent effect for both diluents were seen in dilution 90% and 80% that the none of bacteria shown any inhibition zone. Attention to amount of oily propolis in dilution, methanol as diluent cause less amount of propolis and more bactericidal effect compare to DMSO, while recent paper indicated DMSO has more effect [10]. Some studies indicated Gram-negative bacteria, such as Pseudomonas aeruginosa was resistance to the bactericidal effect of propolis, but the determined inhibitory zone indicated that both Gram-positive and negative bacteria are sensitive to the studied propolis preparations, even Gram-negative bacteria are more sensitive.…”
Section: Discussionmentioning
confidence: 98%
“…The percentage represented by the difference between Gammaproteobacteria and Enterobacteriaceae can be related to those bacteria linked to variable performance, considering that it has been demonstrated as having better feed conversion ratio in birds with an abundance of this class due to the difference in number of sequences of members of Escherichia and Shigella (Singh et al., ). Previously published study has shown that propolis could decrease the amount of Salmonella and E. coli in vitro (Netíková et al., ). A decrease in the amount of Enterobacteriaceae in caecal samples of chickens that consumed 400 ppm of RP was observed compared to those consuming 100 and 200 ppm of RP.…”
Section: Discussionmentioning
confidence: 96%
“…El agua, etanol, metanol, propanol, acetato de etilo, ácido acético son solventes polares especiales para solubilizar los componentes de propóleos; sin embargo, el alcohol etílico es reconocido como el mejor solvente para retirar sus principios activos [20,21]. Los extractos del etanol tienen actividad antibacteriana más alta comparada con los extractos acuosos, y la actividad antibacteriana depende de su origen y de la especie bacteriana evaluada [22].…”
Section: Introductionunclassified